Hanging-wall deformation and gas-migration associated to a major salt detaching fault in the Norwegian Danish Basin. (October 2015) - Clausen, O.R.; Andresen, K.J.; Mauritzen, E.K.; Connolly, D.; Korstgård, J.A.
Abstract: The central and southern regions of the North Sea Basin are characterized by mobile Zechstein Salt and represent an excellent area to study listric normal fault development related to halokinesis. The North Sea Basin–in spite of being a mature explored hydrocarbon producing basin-contains a generally not fully understood hydrocarbon plumbing system. Faults and associated fluid migration routes represent critical elements of the plumbing system. Here we present a combined 3D seismic mapping of a listric fault and detailed seismic attribute analysis of shallow gas anomalies near the fault implying a close and complex relationship between a major detaching fault, hangingwall deformation and fluid migration and entrapment. The fault and associated antithetic and secondary synthetic faults is controlled by the growth of the underlying salt structure. Three separate segments of the fault are recognized showing distinct and varying characteristics of structural maturity and fluid migration. The studied fault and shallow gas anomalies thus represent an example of a complex faulted shallow fluid migration system developing in relation to an underlying salt structure which could be relevant for understanding similar salt, fault and fluid migration systems around the world. Highlights: 3D seismic analysis of the hangingwall deformation at a salt related listric fault. Integration of structural analysis and fluid migration along and across faults. 3D seismic attribute analysis and neural network used for structural analysis. A new conceptual model for late HC migration in the western Norwegian-Danish Basin.